Exploring the Potential of Interferon Gamma Gene as Major Immune Responder for Bovine Tuberculosis in River Buffalo. (7th April 2021) - Javed, Maryam; Raza, Syed Ahmed; Nadeem, Asif; Ali, Muhammad Muddassir; Shehzad, Wasim; Mehmood, Khalid
Abstract : Bovine tuberculosis (bTB) is a widespread zoonotic infection targeting the livestock sector, especially in developing countries, and posing a risk to humans and animal populations. Its recent prevalence in river buffaloes has been estimated as higher as 33.7%. In emergent countries like Pakistan, there is likeliness of human-livestock interfaces extensively and lacking of effective preventive measures that illustrate the risk of spreading the infection at a remarkable rate. The river buffalo ( Bubalus bubalis ) is an upkeep host of Mycobacterium bovis and is responsible for disease transmission among buffaloes and other livestock species. In this study, potential molecular biomarkers in the Interferon-gamma gene (IFNg) were identified after genomic screening of river buffaloes. Unique genomic loci in river buffalo proved the novelty of the genomic structure of this phenomenal animal but also highlighted its significance in natural immunity against the Mycobacterium . A total of eight single nucleotide polymorphisms were identified in the coding region of IFNg. The SNPs in the exonic region were all transitions, i.e., the conversion of purines to purines. These SNPs were analyzed for Hardy Weinberg Equilibrium, chi 2 test, gene diversity, and protein structural conformation. Pathway analysis in tuberculosis revealed that IFNg inhibits the antigen-presenting cells (APC) through JAK and STAT pathways. Network analysis of IFNg proteins in both species showed strong associations among the immunity-related proteins (interleukins, tissue necrosis factors) and receptors of interferons. The identified polymorphic sites might be novel-potentiated markers for the selection of animals with superior immune response against bTB and can be exploited as promising genomic sites for breeding the resistant animal herds to combat Mycobacterium infection in a long run.